2018
DOI: 10.1097/rlu.0000000000001975
|View full text |Cite
|
Sign up to set email alerts
|

Virchow Node From Prostate Carcinoma by 18F-Choline PET/CT

Abstract: F-choline PET/CT is increasingly being used during the follow-up of prostate cancer and is bringing us valuable information for the delineation of local and distant nodal recurrence in patients with hormone-resistant poorly differentiated cell types. Lymphatic spreading usually involves pelvic and retroperitoneal levels, being unusual at supraclavicular levels. We report a 75-year-old man with unsuspected involvement of Virchow node from prostate cancer observed using F-choline PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…One previous study also reported that 3.2% of the treatmentnaïve patients have LNMs in the Virchow nodes (8). The study showed that the Virchow nodes were significantly more frequent with a GS ≥8 as compared to a GS ≤7b primary PC tumor (8,42).…”
Section: Discussionmentioning
confidence: 79%
“…One previous study also reported that 3.2% of the treatmentnaïve patients have LNMs in the Virchow nodes (8). The study showed that the Virchow nodes were significantly more frequent with a GS ≥8 as compared to a GS ≤7b primary PC tumor (8,42).…”
Section: Discussionmentioning
confidence: 79%
“…In recent decades, multiple reports have been published wherein the latest imaging modalities have uncovered VTN otherwise not clearly revealed on physical examination [24][25][26] Cham et al [25] reported a 56-year-old man with a recent diagnosis of distal esophageal carcinoma, in whom whole-body F-18 FDG scintigraphy was performed for staging. The scintigraphy had shown a large primary carcinoma of the mid-to-distal esophagus above the level of the gastroesophageal junction, two normal-size right retrocrural nodes, and left supraclavicular adenopathy (VTN).…”
Section: Virchow-troisier's Node and Latest Imaging Modalitiesmentioning
confidence: 99%
“…The scintigraphy had shown a large primary carcinoma of the mid-to-distal esophagus above the level of the gastroesophageal junction, two normal-size right retrocrural nodes, and left supraclavicular adenopathy (VTN). de la Riva-Pérez et al [26] reported a 75-yearold man with unsuspected involvement of VTN from prostate cancer observed using F-choline PET/CT. El Salvador Atlas of Gastrointestinal Video Endoscopy (https://www.gastrointestinalatlas.…”
Section: Virchow-troisier's Node and Latest Imaging Modalitiesmentioning
confidence: 99%